Aquatic Exercise Training Outcomes on Functional Capacity, Quality of Life, and Lower Limb Lymphedema: Pilot Study - Dionne, Andrée; Goulet, Serge; Leone, Mario; Comtois, Alain-Steve (The journal of alternative and complementary medicine (New York, N.Y.), 2018)
To investigate whether patients with lower limb lymphedema (LLL) can benefit from water immersion exercise training to improve functional capacity, quality of life (QOL), and help control/diminish limb volume. A before-after trial. A community University Sports Center. Eleven participants were recruited to participate and four declined to pursue the study for personal reasons. A convenient sample of seven female affected by either bilateral or unilateral LLL volunteered for this pilot study. Patients had primary or secondary lymphedema as complications of melanoma or gynecologic cancers. An aquatic training exercise intervention of moderate to vigorous intensity was conducted for a 6-week period (12 sessions of 45 min). This innovative circuit training program consisted of yoga exercises, aqua-jogging, pedaling on a water bike, and muscular training on an aquastep and a trampoline. The physical characteristics of water could be used to overcome the physical and medical limitations encountered on dry land for patients with LLL to exercise and reach training benefits. Outcome measures were the 6-min walk test (6MWT), handgrip strength test, QOL for limb lymphedema questionnaire (LYMQOL), bioelectrical impedance spectroscopy, and limb circumference. The distance covered in the 6MWT and the handgrip strength were significantly improved. A trend toward an increase in the overall QOL score was noticeable, whereas a significantly improved emotions score was observed with the LYMQOL questionnaire. Limb circumferential volume was significantly lower and impedance was increased, denoting a decrease in lymphatic fluid. Innovative aquatic exercise training program allows moderate and vigorous intensity activities for patients with LLL, increases functional capacity and QOL. Thus, immersion exercise does not appear to exacerbate LLL and a randomized clinical trial with larger numbers is essential to consolidate the results of this study.